2015
DOI: 10.3354/ame01723
|View full text |Cite
|
Sign up to set email alerts
|

New lipid envelope-containing dsDNA virus isolates infecting Micromonas pusilla reveal a separate phylogenetic group

Abstract: Combined, these characteristics allowed classification of the MpVs into two groups.Exposure to chloroform led to loss of infectivity by all MpVs in one group, which suggests the presence of an outer lipid envelop. In addition, all except one of the members in that group formed a monophylogenetic clade that was distinct from all 35 other MpV isolates. The distinctive characteristics of the two MpV groups suggest different infection strategies, which may have important implications for the ecology of both host a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…At temperatures lower than T opt , MicV-B propagated and killed their hosts through cell lysis as classically reported in the literature (Mayer and Taylor, 1979;Zingone et al, 2006;Baudoux et al, 2015;Martínez-Martínez et al, 2015). Yet the kinetics and the intensity of viral replication slowed down with decreasing temperatures.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…At temperatures lower than T opt , MicV-B propagated and killed their hosts through cell lysis as classically reported in the literature (Mayer and Taylor, 1979;Zingone et al, 2006;Baudoux et al, 2015;Martínez-Martínez et al, 2015). Yet the kinetics and the intensity of viral replication slowed down with decreasing temperatures.…”
Section: Discussionmentioning
confidence: 73%
“…These approaches have shown that temperature may influence the infection process by regulating viral abundance and infectivity. Most marine virus isolates tolerate low temperatures whereas increasing temperatures tend to induce loss in infectivity and ultimately inactivation of the viral particles (Nagasaki and Yamaguchi, 1998;Baudoux and Brussaard, 2005;Tomaru et al, 2005;Martínez-Martínez et al, 2015). Nevertheless, as viruses generally exhibit a broader thermotolerance than their hosts (Mojica and Brussaard, 2014), and because the optimal temperature for lytic replication (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In short, samples were diluted 200-1000-fold using a 2 M TrisHCl buffer at pH 8 and viruses were stained using the nucleic acid-specific fluorescent dye SYBR Green I (Molecular Probes R , Life Technologies, Thermo Fisher). Raw data were analyzed using Cytowin (Vaulot, 1989;Version 4.31 available at http:// application.sb-roscoff.fr/Phyto/index.php), whereby PgV and MpV were easily discriminated by plotting green nucleic acidspecific fluorescence vs. side scatter (Baudoux and Brussaard, 2005;Martínez et al, 2015).…”
Section: Analysesmentioning
confidence: 99%